Optimizing the preparation of Cross-Linked Enzyme Aggregates (CLEA)- amylase from supermeal worm (Zophobas morio) - Easa, Muhammad Noor; Yusof, Faridah (Asian Research Publishing Network (ARPN), 2015)
Cross-linked enzyme aggregates (CLEA) technology has been gaining more attention recently due to their advantages in industrial application. Various CLEA- enzymes has been successfully prepared with diverse advantages. Among the benefits of CLEA are; more stability, easy to prepare, cheap and reusable as compared to the free enzymes. This particular study has attempted to optimize the production of CLEA-amylase, which sourced from supermeal worm protein extract. One Factor at a Time (OFAT) and Response Surface Methodology (RSM) had been used to achieve the goal. Screening of several additives had been conducted to enhance the recovery activity of CLEA- amylase. The final preparation of CLEAamylase was done by applying acetone as precipitant, glutaraldehyde as cross-linking agent and BSA as proteic feeder. Under Face Centered Central Composite Design (FCCCD), the interactions between those three influential parameters were observed. From the 20 runs, the optimum activity was recorded at Run 11 (26.65%), under the condition of using 60% acetone, 90mM glutaraldehyde and 2.5 mg/ml bovine serume albumin (BSA) as additive. The model equation was considered valid after been tested through validation test. Acetone and glutaraldehyde concentration had shown the most dominant factor from this study, while BSA concentration had insignificant effects.